Pengaruh Pemberian Mulsa dan Pengaturan Jarak Tanam Terhadap Pertumbuhan Jagung Manis (Zea mays saccharata Sturt.) - Deva Pratiwi Ayu Lestari; Didik Utomo Pribadi; Sutini Sutini (Program of Biology Education, Universitas Lambung Mangkurat, 2023)
Corn is a horticultural commodity that people love because it contains a lot of high-quality nutrition and is beneficial for human health. One of the examples is sweet corn. Sweet corn is usually planted in a plateu, and it needs some environmental manipulation to be planted in a low plain. The purpose of this research is to find out about the role of mulch and plant space setting, with the hope that organic mulch and plant space setting will produce good results for plants and that sweet corn will grow in the low plain productively both in quantity and quality. The research is held in a moorland at Pabian, Sumenep, Madura with an altitude of Â±500 meters above sea level. This research is a factorial experiment that is arranged based on a split plot design (SPD) that consists of two factors. Factor 1 is the use of mulch as a subplot that consists of no mulch (control), rice straw mulch, and plastic mulch. Factor 2 is plant space on the main plot. The interaction between the two treatments above has a significant effect on the leafâ€™s chlorophyll and the number of cob seeds. The average treatment plant spacing is 70 x 40, and the plastic mulch gives good growth and results.